Members of the microRNA-17-92 cluster exhibit a cell-intrinsic antiangiogenic function in endothelial cells - Döbele, Carmen; Bonauer, Angelika; Fischer, Ariane; Scholz, Alexander; Reiss, Yvonne; Urbich, Carmen; Hofmann, Wolf-Karsten; Zeiher, Andreas M.; Dimmeler, Stefanie (Blood, 2010)
MicroRNAs are endogenously expressed small noncoding RNAs that regulate gene expression on the posttranscriptional level. The miR-17-92 cluster (encoding miR-17, -18a, -19a/b, -20a, and miR-92a) is highly expressed in tumor cells and is up-regulated by ischemia. Whereas miR-92a was recently identified as negative regulator of angiogenesis, the specific functions of the other members of the cluster are less clear. Here we demonstrate that overexpression of miR-17, -18a, -19a, and -20a significantly inhibited 3-dimensional spheroid sprouting in vitro, whereas inhibition of miR-17, -18a, and -20a augmented endothelial cell sprout formation. Inhibition of miR-17 and miR-20a in vivo using antagomirs significantly increased the number of perfused vessels in Matrigel plugs, whereas antagomirs that specifically target miR-18a and miR-19a were less effective. However, systemic inhibition of miR-17/20 did not affect tumor angiogenesis. Further mechanistic studies showed that miR-17/20 targets several proangiogenic genes. Specifically, Janus kinase 1 was shown to be a direct target of miR-17. In summary, we show that miR-17/20 exhibit a cell-intrinsic antiangiogenic activity in endothelial cells. Inhibition of miR-17/20 specifically augmented neovascularization of Matrigel plugs but did not affect tumor angiogenesis indicating a context-dependent regulation of angiogenesis by miR-17/20 in vivo.
Gesehen am 15.05.2023